Peningkatan Hasil Belajar Pendidikan Agama Kristen melalui Metode Pembelajaran TALKING STICK - Novrida Nenoliu; Junaity Soften Sine; Irene Sondang Ully; Sance Mariana Tameon (Widyadewata, 2023)
This study aims to determine the increase in learning outcomes of Christian Religious Education through the talking stick method for students at SD Inpres Nunumeu. using Classroom Action Research (CAR) research with the implementation of 2 cycles. Data collection techniques used are observation, tests, and documentation. The research subjects were 20 students of class VA. The results of this study are the observation of teacher activity in Cycle I, namely 72.7 with good category and cycle II, namely 91 with very good category, the increase is 18.3, while the observation of student activity in cycle I is 58.4 with sufficient category and in cycle II is 82.7 with very good category then the increase is 24.3, and student learning outcomes, namely the first cycle is 69.5 in the good category and the second cycle is 81.2 with the very good category so that it increases by 11.7 successfully exceeding the school KKM which is 75 and the completeness of the classification of students in the first cycle is 47.50% and the second cycle is 85% has exceeded the completeness of the school classification, which is 75%.